Landscape of germline cancer predisposition mutations testing and management in pediatrics: Implications for research and clinical care - Shahani, Shilpa A.; Marcotte, Erin L. (Frontiers in Pediatrics, 2022)
As germline genetic testing capacities have improved over the last two decades, increasingly more people are newly diagnosed with germline cancer susceptibility mutations. In the wake of this growth, there remain limitations in both testing strategies and translation of these results into morbidity- and mortality-reducing practices, with pediatric populations remaining especially vulnerable. To face the challenges evoked by an expanding diversity of germline cancer mutations, we can draw upon a model cancer-associated genetic condition for which we have developed a breadth of expertise in managing, Trisomy 21. We can additionally apply advances in other disciplines, such as oncofertility and pharmacogenomics, to enhance care delivery. Here we describe the history of germline mutation testing, epidemiology of known germline cancer mutations and their associations with childhood cancer, limitations, and future directions for research and clinical care.